Energy budget of forming clumps in numerical simulations of collapsing clouds - Camacho, Vianey; Vázquez-Semadeni, Enrique; Ballesteros-Paredes, Javier; Gómez, Gilberto C.; Fall, S. Michael; Mata-Chávez, M. Dolores (The astrophysical journal, 2016)
We analyze the physical properties and energy balance of density enhancements in two SPH simulations of the formation, evolution, and collapse of giant molecular clouds. In the simulations, no feedback is included, so all motions are due either to the initial decaying turbulence or to gravitational contraction. We define clumps as connected regions above a series of density thresholds. The resulting full set of clumps follows the generalized energy equipartition relation, , where is the velocity dispersion, R is the “radius,” and Σ is the column density. We interpret this as a natural consequence of gravitational contraction at all scales rather than virial equilibrium. Nevertheless, clumps with low Σ tend to show a large scatter around equipartition. In more than half of the cases, this scatter is dominated by external turbulent compressions that assemble the clumps rather than by small-scale random motions that would disperse them. The other half does actually disperse. Moreover, clump sub-samples selected by means of different criteria exhibit different scalings. Sub-samples with narrow Σ ranges follow Larson-like relations, although characterized by their respective values of Σ. Finally, we find that (i) clumps lying in filaments tend to appear sub-virial, (ii) high-density cores ( cm3) that exhibit moderate kinetic energy excesses often contain sink (“stellar”) particles and the excess disappears when the stellar mass is taken into account in the energy balance, and (iii) cores with kinetic energy excess but no stellar particles are truly in a state of dispersal.
Gesehen am 28.04.2020